Analısıs Kualıtatıf Rhodamın B pada Perona Mata (Eyeshadow) yang Beredar dı Toko Kosmetık Kota Tarakan - Rendi Antika; Faizal Mustamin; Irma Novrianti (Journal Borneo, 2024)
Both adults and teenagers often use eyeshadow as a common cosmetic. The paint and textile industry often uses a red synthetic dye known as rhodamine B. Apart from having carcinogenic properties, continued use of rhodamine B can cause liver problems and gastrointestinal irritation which has the potential to hurt health. This research aims to answer the problem, of whether or not eyeshadow preparations sold in Tarakan City beauty shops contain Rhodamine B. The method in this research uses a wool thread technique and a rhodamine B rapid test kit to carry out qualitative analysis using eleven samples. The results showed that of the eleven eyeshadow samples examined at the Tarakan City cosmetics shop, three samples experienced a color change from red to dark red or purplish. Two of the eyeshadows are not registered, while one is registered with BPOM. Based on these findings, it can be concluded that three of the eleven eyeshadow samples tested positive for rhodamine B.